Component Interaction of ESCRT Complexes Is Essential for Endocytosis-Dependent Growth, Reproduction, DON Production and Full Virulence in Fusarium graminearum - Xie, Qiurong; Chen, Ahai; Zhang, Yunzhi; Yuan, Mingyue; Xie, Wei; Zhang, Chengkang; Zheng, Wenhui; Wang, Zonghua; Li, Guangpu; Zhou, Jie (Frontiers in Microbiology, 2019)
Multivesicular bodies (MVBs) are critical intermediates in the trafficking of ubiquitinated endocytosed surface proteins to the lysosome/vacuole for destruction. Recognizing and packaging ubiquitin modified cargoes to the MVB pathway require ESCRT (Endosomal sorting complexes required for transport) machinery, which consists of four core subcomplexes, ESCRT-0, ESCRT-I, ESCRT-II and ESCRT-III. Fusarium graminearum is an important plant pathogen that causes head blight of major cereal crops. Our previous results showed that ESCRT-0 is essential for fungal development and pathogenicity in Fusarium graminearum. We then, in this study, systemically studied the protein-protein interactions within F. graminearum ESCRT-I, -II or -III complex, as well as between ESCRT-0 and ESCRT-I, ESCRT-I and ESCRT-II, and ESCRT-II and ESCRT-III complexes and found that loss of any ESCRT component resulted in abnormal function in endocytosis. In addition, ESCRT deletion mutants displayed severe defects in growth, deoxynivalenol (DON) production, virulence, sexual and asexual reproduction. Importantly genetic complementation with corresponding ESCRT genes fully rescued all these defective phenotypes, indicating the essential role of ESCRT machinery in fungal development and plant infection in F. graminearum. Taken together, the protein-protein interactome and biological functions of the ESCRT machinery is first profoundly characterized in F. graminearum, providing a foundation for further exploration of ESCRT machinery in ﬁlamentous fungi.